2011
DOI: 10.1007/s13280-011-0212-y
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Face of Arctic Snow Cover: A Synthesis of Observed and Projected Changes

Abstract: Analysis of in situ and satellite data shows evidence of different regional snow cover responses to the widespread warming and increasing winter precipitation that has characterized the Arctic climate for the past 40-50 years. The largest and most rapid decreases in snow water equivalent (SWE) and snow cover duration (SCD) are observed over maritime regions of the Arctic with the highest precipitation amounts. There is also evidence of marked differences in the response of snow cover between the North American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
215
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(238 citation statements)
references
References 57 publications
(72 reference statements)
7
215
0
1
Order By: Relevance
“…Recent studies based on satellite and in-situ observations have shown that rapid winter/spring warming and changes in interdecadal climate modes since around 1991 have led to a significant decline in snowpack accumulation and snow cover duration across most of Alaska and Canada despite increasing winter precipitation [36][37][38]94,95]. In some regions of the North American Cordillera, the recent loss of snowpack is unprecedented over the past millennium [96].…”
Section: Drivers Of Vegetation Greening and Browning Trendsmentioning
confidence: 99%
“…Recent studies based on satellite and in-situ observations have shown that rapid winter/spring warming and changes in interdecadal climate modes since around 1991 have led to a significant decline in snowpack accumulation and snow cover duration across most of Alaska and Canada despite increasing winter precipitation [36][37][38]94,95]. In some regions of the North American Cordillera, the recent loss of snowpack is unprecedented over the past millennium [96].…”
Section: Drivers Of Vegetation Greening and Browning Trendsmentioning
confidence: 99%
“…Many studies on snow depth have focused on local and regional scales over Russia (Ye et al, 1998;Kitaev et al, 2005;Bulygina et al, 2009Bulygina et al, , 2011Brasnett, 1999) and the Tibetan Plateau (TP) (Li and Mi, 1983;Ma and Qin, 2012) and have revealed significant regional changes. It has been reported that annual mean snow depth has increased in northern Eurasia and the Arctic during the last 70 years (Ye et al, 1998;Kitaev et al, 2005;Callaghan et al, 2011;Liston and Hiemstra, 2011) with large regional differences (Bulygina et al, 2009(Bulygina et al, , 2011Ma and Qin, 2012;Stuefer et al, 2013;Terzago et al, 2014). Changes in snow depth are primarily affected by air temperature and precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Arctic ecosystems have experienced an intensified warming tendency, reaching almost twice the global average (ACIA, 2005;AMAP, 2011;Callaghan et al, 2012c;Serreze and Barry, 2011). The projected Arctic warming is also expected to be more pronounced in coming years (AMAP, 2011;Callaghan et al, 2012a;Christensen et al,4468 E. López-Blanco et al: Exchange of CO 2 in Arctic tundra perature, precipitation and growing season length will likely increase in the Arctic (ACIA, 2005;Christensen et al, , 2004IPCC, 2007). Given this situation, an improvement in our process-based understanding of CO 2 exchanges in the Arctic and their climate sensitivity is critical (McGuire et al, 2009).…”
Section: Introductionmentioning
confidence: 99%